An Evaluation of a Commercialized mHealth Intervention to Promote Physical Activity in the Workplace - Di Sebastiano, Katie M.; Lau, Erica Y.; Yun, Lira; Faulkner, Guy (Frontiers in Public Health, 2022)
UPnGO with ParticipACTION (UPnGO) was a commercialized 12-month workplace physical activity intervention, aimed at encouraging employees to sit less and move more at work. Its design took advantage of the ubiquitous nature of mobile fitness trackers and aimed to be implemented in any office-based workplace in Canada. The program was available at cost from June 2017- April 2019. The objectives of this study are to evaluate the program and identify key lessons from the commercialization of UPnGO. Methods: Using a quasi-experimental design over 3 time points: baseline, 6 months, 12 months, five evaluation indicators were measured as guided by the RE-AIM framework. Reach was defined as number of organizations participating, number and percentage of employees who registered for UPnGO at those organizations, and the number and percentage of sedentary participants registered. Effectiveness was assessed through average daily step count. Adoption was determined by Workplace Champion and senior leadership responses to the off-platform survey. Implementation was assessed as the percentage of participants who engaged with specific program elements at the 3-evaluation time points. Maintenance was assessed by the number of companies who renewed their contracts for UPnGO. Results: Reach Seventeen organizations and 1980 employees participated in UPnGO, with 27% of participants identified as sedentary at baseline. Effectiveness Daily step count declined from 7116+/-3558 steps at baseline to 6969+/-6702 (p=<0.001) at 12 months. Adoption Workplace Champion and senior leadership engagement declined from 189 to 21 and 106 to 5 from baseline to 12 months respectively. Maintenance Two companies renewed their contracts beyond the first year. Conclusions: The commercialization of UPnGO was an ambitious initiative that met with limited success; however, some key lessons can be generated from the attempt. The workplace remains an important environment for PA interventions but effective mHealth PA programs may be difficult to implement and sustain long-term.